Diseño de un paquete aerodinámico para un vehículo de carreras MRT1 (2016)
In this project was the study of the "Design of a package aerodynamic for a racing car MRT1" seeking to optimize the distribution of air generating "suction", meaning an adhesion of the vehicle to the ground, making it more stable in competition, this project has been realized for the company Ford Motor Colombia. After obtained data from the specifications of the aerodynamic model package as dimensions, speed of air, among others. Manufacture and Assembly plans were carried out.